A High-Performance Solution-Processed Organic Photodetector for Near-Infrared Sensing - Huang, Jianfei (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.